The legitimacy and impact of business schools: key issues and a research agenda - Pettigrew, Andrew; Starkey, Kenneth (Academy of Management, 2016)
It is an appropriate moment to review research into the legitimacy and impact of business schools. It is more than a decade now since Pfeffer and Fong's (2002) provocative paper challenging the perceived orthodoxy of business school success in the very first edition of the Academy of Management Learning & Education.